Performance of Lettuce (Lactuca Sativa L.) Genotypes with Respect to Morphological, Yield and Quality Traits at Two Localities of Nepal - Dahal, Januka; Pandey, Utshay; Bhandari, Upakar; Tiwari, Sabina; Shrestha, Suchit (Nepalese Horticulture, 2021)
Lettuce is cultivated as minor crop in Nepal. However, people are becoming more health conscious in these days and demand for salad is increasing in food. The demand of lettuce is also gradually increasing but relatively few farmers are involved in this crop due to the lack of high-yielding and good quality genotypes. The research was conducted at two locations of Nepal; Kavre and Kaski with the aim of evaluating the performance of seven different hybrid lettuce genotypes in terms of its morphology, yield, and quality. The research was laid out on Randomized Complete Block Design with three replications at each location. Two types of lettuce were used on the research i.e. head type and leaf type. Among the head type, genotype Iceberg performed better with more plant spread (51 cm), head diameter (14.7 cm) and yield (738.4 g at Kavre and 725.8 g at Kaski) than other head type lettuce genotypes and among leaf type variety Green Oak was recorded with highest numbers of leaves (67 at Kavre and 40 at Kaski) and yield (572.3 g at Kavre and 641.9 g at Kaski). So, among head type lettuce genotypes Iceberg performed better as this had better plant spread, large head diameter, more yield and sweet flavor. Among leaf type genotypes Variety Green Oak was found most suitable for Nepali Market as this variety had highest number of leaves and yield among leaf type lettuce genotypes.